Cuidado transicional no hospital - domicílio para pessoas idosas com doenças crônicas não transmissíveis - Cavalcanti, Larissa dos Santos (2022)
Introduction: Population aging is a global reality and together with it we have a greater occurrence of Non-Communicable Chronic Diseases (NCDs), so the elderly population needs transitional care from the hospital to the home from the perspective of integrality, within the Network of Health Care (RAS), in order to avoid hospital readmissions, mainly because there is a risk of exacerbation of the disease. Objectives: To evaluate the transition from hospital to home in elderly people with Chronic Non-Communicable Diseases. Method: descriptive and cross-sectional study with 105 elderly/caregivers with chronic diseases who were discharged from the medical clinic and surgical clinic of a university hospital. After approval by the Research Ethics Committee (CAAE: 40618020.6.0000.5183), data collection was performed by telephone using the adapted version of the CTM-15 from August to November 2021. For data analysis, statistics from mean, median, standard deviation, minimum and maximum, as well as the shapiro-wilk normality test. Results It was identified that the majority were male 62 (59.05%), had 1 to 9 years of schooling 58 (55.24%), with the most prevalent comorbidity being cancer 65 (61.90%), hypertensive diseases 52 (49.52%), diabetes mellitus 31 (29.52%), had an average hospital stay of 8.7 days and the main respondent of the instrument was the caregiver 66 (62.86%). The average score of the MTC – 15 was 58.24, a value considered low quality of transition. The factor with the best score was the one related to the importance of preferences, which obtained the highest estimates of maximum value and the fact that the care plan was the minimum, also highlights – if the low average for guidelines, the side effects of medications. Conclusion: The transition of care in the inpatient units (medical and surgical clinic) of the university hospital occurs with low quality. Satisfaction with the health objective achieved was observed in the evaluation, however, there were weaknesses in the provision of guidelines on care plans that were not just the delivery of exams and appointments, in addition to the lack of guidance on the side effects of the treatments. medications. In the literature, difficulties, weaknesses and challenges can be seen, as well as a gap in national studies on the subject.